The Role of Women in Islamic Politics: From the Early Period to the Contemporary Era through the Lens of Kimberlé Crenshaw's Intersectionality Perspective - Nisa’, Ihda Shofiyatun; Shapiulayevna, Aliyeva Patimat; Fikri, M. Najib (Kawanua International Journal of Multicultural Studies, 2024)
This study explores the development of women's roles in Islamic politics from the early Islamic era to the contemporary period using Kimberlé Crenshaw's intersectionality framework. This theory is employed to analyze how Muslim women navigate layered discrimination at the intersection of gender, religion, and other social structures. Data were obtained through literature reviews and analyzed descriptively and analytically. The findings reveal that during the early Islamic period, women like Khadijah and Aisha played strategic roles in the economy, politics, and education. Khadijah provided financial support to Prophet Muhammad, while Aisha made significant contributions to political decision-making and the dissemination of knowledge, such as the Prophet Muhammad’s hadiths. In the contemporary era, the involvement of Muslim women has become increasingly diverse, encompassing formal positions such as heads of state, parliament members, and social activists. For instance, in Indonesia, figures like Megawati Soekarnoputri, Puan Maharani, and Sri Mulyani exemplify inclusive political representation by women. The intersectionality theory reveals that Muslim women face complex discrimination within patriarchal structures but have also leveraged education, technology, and social media to expand their influence. Despite progress, challenges such as resistance to changing gender roles and limited political representation persist. This research contributes by offering a new perspective on gender and Islamic politics, while also providing a foundation for further studies on women's strategies in fostering a more equitable and inclusive society.